Sclerotherapy for III- and IV-degree hemorrhoids: Results of a prospective study - Lisi, Giorgio; Gentileschi, Paolo; Spoletini, Domenico; Passaro, Umberto; Orlandi, Simone; Campanelli, Michela (Frontiers in Surgery, 2022)
Background: During the last two years anorectal surgery has been strongly affected and even surgery for urgent cases cannot be scheduled, also patients with III- and IV- degree bleeding hemorrhoids should be treated conservatively. The aim was to evaluate the effectiveness of sclerotherapy in those patients who had to postpone surgery. Methods: We included all patients with third- and fourth- degree bleeding hemorrhoids underwent outpatient sclerotherapy. The Visual Analog Scale and the Hemorrhoid Severity Score was used at the base-line, at 4 weeks after the procedure with telephone interview, and all patients were outpatient evaluated 1 week, 1 months and 1 year after the treatment. All pre- and post- operative data were recorded. Results: From October 2020 to November 2021 a total of 19 patients with third- (12 pts; 63%) and fourth- degree (7 pts; 37%) bleeding hemorrhoids were enrolled. The mean operative time was 4.5 minutes, and no intraoperative complications were occurred. One case of tenesmus and three failures were detected. Six months after the procedure, the overall success rate was 84% despite at the end of the study period all the patients enrolled reported persistent bleeding. Of these, five patients (26%) were scheduled for surgery and eleven patients (58%) refused surgery and asked to underwent a re – do sclerotherapy. Conclusion: Sclerotherapy with 3% polidocanol foam is a safe and effective procedure also in III- and IV- degree bleeding hemorrhoids. The long-term data on the length of the foam remain to be evaluated in additional studies.